Union Wage Dispersion Magnitude and Trend Before and After the 2008 Financial Crisis - Heydarirad, Azadeh (Université d'Ottawa | University of Ottawa, 2016)
Over the past two decades the Canadian Labour market experienced a rise in the overall wage inequality and de-unionization. This paper provides empirical evidence on effects of unionization on the real hourly wage before and after the 2008 financial crisis in Canada. The Ordinary Least Square (OLS) model is used to estimate the impact of union status and time related (such as time trend, year, and post-2008) variables on the real hourly wage level. Moreover, Heckman’s two- step approach is performed to correct for non-random sample selection. The findings show unionization affects the real hourly wage positively, while the time variables’ coefficients indicate the 2008 financial crisis did not have a significant impact on the real hourly wage level in Canada.